Telephone: a novel (Tantor Media, Inc., Graywolf Press, 2023)
"Zach Wells, a laconic geolist-slash-paleobiologist, has the trappings of a comfortable life, yet is not contented. He's expert in the geological history of a cave in the Grand Canyon, but less so where his wife and daughter are concerned. And when his daughter develops unusual vision problems and has a seizure, the world of this family of three crumbles. Powerless in the face of his daughter's slow deterioration, Wells finds a note asking for help tucked into a jacket he's ordered online, and sets off on a quixotic rescue mission."--Provided by publisher.